To find where the function intersect with the x-axis, then we need to substitute with x=0
2(0) +2y =-6
==> 2y = -6\
==> y=-3 or he function intersect with x-axis at the point (0,-3)
Now to find out where the function intersect with y-axis, then y will be 0:
2x+ 2(0) =-6
==> x= -3 (the function intersect with y=axis at the point (-3,0)
Since this equation is in standard form we can answer this by allowing both x and y to equal zero, one at a time. Starting with x=0 we get the equation
0x+2y=-6 or 2y=-6
divide both sides of the equation by 2 and we get
y=-3 so the coordinates of the y intercept will be (0,-3)
Now start with the original equation again, and let y=0 and we get
2x+0y=-6 or 2x=-6
divide both sides of the equation by 2 (the x coefficient) to get x=-3 and the coordinates of the x intercept will be (-3,0)
Therefore, the x and y intercepts of the equation 2x+2y=-6 are (-3,0) and (0,-3)
find the x-intercept and the y-intercept for the graph of the equation 2x+2y=-6
to find the x-intercept solve for x and to find the y intercept solve for y
x intercept (y=0)
2x + 2(0) = -6
2x = -6
divide by 2 to get rid of the 2 in front of the x
`(2x)/2 = -6/2 `
x intercept = -3,0
y intercept (x=0)
2y = -6
just like last time divide by 2 to get y alone
2y / 2 = -6/2
y intercept = 0,-3
y-intercept=-3 and x-intercept= -3
To find the intercepts of a graph with an axis , we have to calculate f(x)=0 and f(0).
When calculating f(x)=0, we'll find the interception of the graph with x axis.
We'll re-write the given equation:
We'll isolate the term in y, to the left side:
2y = -6-2x
We'll divide by 2:
y = -3 - x
Now, we'll calculate f(x)=0, that means that y=0.
0 = -3 - x
We'll move x to the left side:
x = -3
The interception point of the graph with x axis is: (-3,0).
Now, we'll calculate the interception point with y axis and for this reason, we'll put x=0.
y = -3 - 0
y = -3
The interception point of the graph with y axis is: (0,-3).
To find the x and y intercept for the graph of 2x+2y = -6.
The intercept of a graph and x axis is got by finding the intersection point on the x axis by putting y= 0 in the equation of the graph and then solving for x. Similarly, by putting x=0 in equation of the graph and solving for y,we get the y intercept.
2x+2(0) = -6 gives 2x = -6 implies x = -6/2 = -3.
So -3 is the x intercept.
2(0)+2y = -6 implies 2y = -6. y = -6/2 = -3.Therefore -3 is the y intercept.